An empirical investigation of brand loyalty behavior among hotel employees in northern Malaysia - Md Salleh, Salniza; Hussin, Zolkafli; Pangil, Faizuniah; Hasan, Hasnizam; Mohd Mokhtar, Sany Sanuri; Shaari, Hasnizam (Centre for Promoting Ideas, 2013)
Employee brand loyalty is essential to all organizations as it could translate into high organizational performance.In order to encourage employees to exhibit loyalty behavior, it has been argued that organizations need to create an environment that is perceived as positive for performance.As such, this paper reports the findings of a study conducted in two hotels to examine the impact of internal market orientation on employee brand loyalty behavior.The findings of this study indicates that only internal intelligence dissemination has an impact on employee brand loyalty behavior